Changes and driving mechanism of water footprint scarcity in crop production: A study of Jiangsu Province, China. (December 2018) - Cao, Xinchun; Huang, Xuan; Huang, He; Liu, Jing; Guo, Xiangping; Wang, Weiguang; She, Dongli
Graphical abstract: Highlights: Water footprint scarcity (WFS) was quantified based on blue-green water availability and appropriation. WFS increased in drought agriculture-based region and dropped in economic developed area. WFS increased in drought agriculture-based region and dropped in economic developed area. Controlling the development of irrigation can reduce WFS and alleviate regional water scarcity. Abstract: The mitigation of water stress in crop production is important for relieving the growing global water shortage. The water footprint scarcity (WFS) for regional water stress evaluation integrating blue and green water resources and the water footprint of the crop production industry were developed in this paper. Three subregions in China, industry-based southern Jiangsu (SJS), agriculture-based northern Jiangsu (NJS) and middle-type central Jiangsu (CJS), were selected to study the spatiotemporal pattern and driving mechanism of WFS. The results show that green water accounts for 56.6% and 71.8% of agricultural water resources available (AWA) and crop water footprint (CWF) of Jiangsu Province. The WFS of Jiangsu was calculated to be 2.26, and almost all prefectures for every year from 1996 to 2015 faced very high water stress (WFS > 1.20). The WFS value increased in NJS and CJS and decreased in SJS over time; meteorological and social factors affected the WFS at the same time. Land irrigation was the main factor to explain the growing water stress in the agriculture-based NJS. The WFS revealed the water shortage more clearly, especially in the water-poor agriculture-based areas, than the results of the conventional water stress index. The strategies for environmental change adaptation suggested by this study are to use WFS for agricultural water suitability evaluation and water resource management policy formulation; to reduce WFS through irrigation efficiency and crop variety promotion worldwide; and to implement compensation measures for agricultural products and virtual water trade to help underdeveloped agricultural production areas improve their agricultural production technology and control irrigation expansion.